Morphology-Controlled Synthesis of Colloidal Polyphenol Particles from Aqueous Solutions of Tannic Acid - Kämäräinen, Tero; Ago, Mariko; Greca, Luiz G.; Tardy, Blaise L.; Müllner, Markus; Johansson, Leena Sisko; Rojas, Orlando J. (ACS Sustainable Chemistry & Engineering, 2019)
The properties and application of particulate systems can be tailored by gaining control on their morphology. Here, a facile method is described for the bottom-up synthesis of biobased colloidal particles with varied morphologies by simple aqueous oxidation of tannic acid used as a precursor in alkaline solutions. Initial tannic acid concentrations of 1-2 wt % produce the largest crystalline yields, while total precipitate yields (up to 64%) are achieved at 2 wt %. Structural and thermochemical evaluations are reported from measurements based on X-ray diffraction and thermogravimetry, as well as infrared, mass, nuclear magnetic resonance, and X-ray photoelectron spectroscopies. The analyses suggest a galloyl-rich composition of the particles with thermal stability up to 450-500 °C. We show that the selection of the base species and pH affords control of the particle morphologies that include rods, platelets, rhomboids, cuboids, and quasi-spherical shapes. The main cause-effect relations are elucidated from principal component analysis of process conditions and particle morphogenetic parameters, which are derived from their physical dimensions and yield. The results indicate an anticorrelation between base countercation ionic radius and particle volume, whereas base strength and initial solution pH correlate with the total precipitate yield and elongated morphologies, respectively.
Created from Fastlane, Scopus look-up
Keywords: Colloidal particles; Crystallization; Morphology control; Polyphenol; Tannic acid